Selection of a lectotype for Brachycrus laticeps mooki Schultz and Falkenbach (Mammalia, Artiodactyla, Merycoidodontidae) - Mader, Bryn J. (Zootaxa, 2017)
In 1968 Schultz and Falkenbach described a new oreodont subspecies, Brachycrus laticeps mooki, from a locality 11 km (7 miles) southeast of Fort Logan, Meagher County, Montana. As a holotype for this new taxon, Schultz and Falkenbach (1968:369) designated both American Museum of Natural History (AMNH) specimen number 21321 (a skull) and AMNH 21322 (a left ramus). Although the citation of two separate catalog numbers as a holotype is highly unusual, Schultz and Falkenbach believed that the specimens cataloged under both numbers represent only a single individual. The use of the term ‘holotype’ was appropriate, therefore, although it would have been more common practice to place elements believed to represent a single individual under a single catalog number. Schultz and Falkenbach did not give a justification for their opinion that AMNH 21321 and AMNH 21322 represent the same individual, although they stated this belief in two publications (1941 and 1968).